O licenciamento ambiental no segmento de exploração e produção offshore de petróleo no Brasil (conceitos, definições, competências e diagnósticos dos processos licenciatórios) - Torres, Ronaldo Chaves (2004)
The objective of this dissertation is to present a critical analysis of the environmental licensing procedures at federal level related to Exploration and Production (E&P) offshore activities in Brazil. The strategy of this analysis was based on the assessment of historical evolution in the environmental licensing procedure since the publication of the Federal Law n° 6.938/ 81. The problems related to environmental licensing at federal level are discussed and solutions are also presented.Based on the conceptual and operation aspects of the environmental licensing procedure, the historical evolution of world environmental questions were described as well as Brazilian environmental licensing procedure, which is the main part of private and public environmental management, and also an instrument of Brazilian Environmental Policy (PNMA), according to Federal Law n° 6.938/ 81.The offshore activities E&P of were studied in this dissertation due to the complexity of environmental licensing procedure that involves legal responsibility at federal, state and municipal levels, and also considering the recent facts in offshore activities E&P of . According to Federal Law n°6.938/ 81, CONAMA Resolutions no 23/ 94 and no 237/ 97, IBAMA is the federal environmental agency responsible for conducting environmental licensing in Brazil, and the CONAMA Resolution n° 237/ 97 is a general rule applied to petroleum environmental licensing procedure.The solution for the problems discussed in this dissertation depend on the negotiation between all interests parts, such as companies, environmental agencies and communities, and the establishment of new rules with the unique objective that is the sustainability of the petroleum business.